Penerapan Terapi Storytelling Digital Mengatasi Kecemasan Pada Anak Usia Pra Sekolah - sari, ria setia; Ranan Salsabila (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
Children who are hospitalized are most likely to feel anxious. They often experience anxiety, such as crying and being afraid of new people, which can hinder their growth. The hospital environment can also cause anxiety and stress. Playing is an activity that children can do with the aim of stimulating the child's growth and development and playing for children in the hospital is a way for children to express their feelings, relax and divert feelings that are difficult to express. Storytelling connects a story to multiple viewers or listeners through sound and clues, also known as a story. The aim of this research is to determine the effect of digital storytelling play therapy on anxiety levels in preschool children in hospitals. The research was conducted with a quasi-experimental design. Sample selection was carried out using the Total Sampling technique, totaling 55 respondents. Data analysis using the PreTest–PostTest test resulted in a P value of 0.00, which means that the conclusion of this research is that there is a significant influence between providing digital storytelling play therapy on anxiety levels. It is hoped that the results of this research will become a reference source for nurses in providing interventions for hospitalized children who experience anxiety.